Development of a GIS based tool to analyze produced water from oil and gas wells and prediction of equilibrium concentrations using CalcAQ - Dhanasekar, Ashwin, author; Carlson, Kenneth H., advisor; Arabi, Mazdak, committee member; Sutton, Sally, committee member (Colorado State University. Libraries, 2013)
New extraction techniques based on hydraulic fracturing and horizontal drilling have significantly increased the available oil and gas in the United States. Producing oil and gas from shale formations is the main source of these unconventional resources. When shale formations are hydraulically fractured to increase the permeability, up to 5 million gallons of water can be used for each well. The significant use of water has caused concerns by several stakeholders, particularly in regions that are constantly facing water shortages such as Texas or Colorado. After the well is fractured, large amounts of water return as frac flowback and then after the well is put into production, water that is coproduced with oil and gas must be collected for the life of the well. The produced water has hazardous characteristics since it has been in contact with oil and gas for millions of years and disposal or reuse is an important part of an oil and gas operation. Current water management for produced water includes underground injection and surface disposal or reuse. Owing to a large amount of total dissolved solids (TDS), metals and hydrocarbons (e.g. BTEX) in the produced water, the brine needs to be treated to achieve acceptable water quality for subsequent disposal or reuse. Reusing and recycling of produced water for drilling and fracturing after appropriate treatment has multiple advantages including less truck traffic and lower fresh water demands. The objective of the research in this thesis was to integrate the OLI chemical equilibrium model into the OWM (Optimized Water Management) tool framework to allow chemical equilibrium calculations to be made for each well and in the aggregate throughout the Wattenberg oil and gas field of northern Colorado. The calculations from this model can then be used as design criteria for treatment train definition based on the desired water disposal outcome. OLI Systems software was developed for the chemical and oil and gas industry and is well suited as a module for calculating chemical equilibrium values for produced water and frac flowback water. The research described in this thesis includes predictions of equilibrium chemistry, solids precipitation and scale forming index, based on water quality data collected in the field. The model can also predict requirements for combining and treating produced water streams to achieve process objectives. At the same time, water quality will be analyzed after detailed sampling from various parts of the field. Finally, water quality after precipitation, settling and filtration has been used to estimate the osmotic pressure and design reverse osmosis processes for different levels of TDS rejection. This will be integrated with a customized ArcGIS tool that will help in predicting treatment specifics on a spatial scale.
Keywords: water tool; produced water; OLI; GIS; CalcAQ